Green infrastructure-based tourism development in a Hungarian case - Edina, Klára Dancsokné Fóris; Krisztina Filepné Kovács; Istvan Valanszki (Fábos Conference on Landscape and Greenway Planning, 2022)
The importance of green infrastructure (GI) has been particularly felt in the pandemic period: the opportunity to spend time and relax outdoors became more valuable for urban residents. There is a strong link between green infrastructure and tourism and recreation, but the ecosystem services of the GI have so far been less emphasized in tourism development planning. GI network elements can be attractions for tourism and sites for recreational activities. However, elements of the GI (such as a greenway) are also elements of tourism and recreation infrastructure. The aim of the present research was to explore the potential of linking GI development and tourism development in a particular tourist area, the Balatonfüred micro-region in Hungary. In our previous research we have already dealt with the GI of this area, especially with the Nivegy Valley and its landscape based tourism development, therefore we chose this region as a sample area for our research. Some of the experience gained here can be generalised: the diverse landscapes with many small values which are not in themselves of great attraction, planned and managed together as a comprehensive network can be attractive for tourists. The view connections revealing in some places and the pleasant hiking trails offer both tourists and locals such a landscape experience that contributes to their physical and mental health. Our specific proposals for GI development and tourism or recreation development in the Nivegy Valley can serve as an example for other areas, showing how well-planned green network can become a resource to serve the growing needs of tourism. At the same time, the proper design and condition of green infrastructure includes opportunities for recreation as well.
Keywords: green infrastructure; tourism; Hungary; Lake Balaton; pandemia